2017
DOI: 10.1016/j.jfa.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Projection functions, area measures and the Alesker–Fourier transform

Abstract: Dual to Koldobsky's notion of j-intersection bodies, the class of j-projection bodies is introduced, generalizing Minkowski's classical notion of projection bodies of convex bodies. A Fourier analytic characterization of j-projection bodies in terms of their area measures of order j is obtained. In turn, this yields an equivalent characterization of j-projection bodies involving Alesker's Fourier type transform on translation invariant smooth spherical valuations. As applications of these results, several basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…For instance, Sheu and Capoferri et al demonstrated quantum projections and pseudo-differential projections, respectively [19,20]. Lau et al and Dorrek et al revealed projections in Banach algebras and projection functions of the Alesker-Fourier transform, respectively [21,22]. Next, Basso reported both maximal projection constants and maximal projections in a threedimensional subspace [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sheu and Capoferri et al demonstrated quantum projections and pseudo-differential projections, respectively [19,20]. Lau et al and Dorrek et al revealed projections in Banach algebras and projection functions of the Alesker-Fourier transform, respectively [21,22]. Next, Basso reported both maximal projection constants and maximal projections in a threedimensional subspace [23].…”
Section: Introductionmentioning
confidence: 99%
“…One of its central inequalities is the Busemann intersection inequality [7], which relates the volume of a star body to that of its intersection body. Intersection bodies were first introduced by Lutwak in [37] and ever since a number of authors has contributed to the research on the duality between projection and intersection bodies (confer [15,18,57] for more details). Recently it was shown by Lu and Leng [27] that inequalities analogous to the Busemann intersection inequality also hold for intersection bodies of all orders.…”
Section: Introductionmentioning
confidence: 99%
“…15), we have for K ∈ K n o and L ∈ S n o ,V p (K, Γ µ p L) = 1 n S n−1 h(Γ µ p L, u) p dS p (K, u) = 1 n(n + p)V n (L) S n−1 S n−1 h(Z µ p (u), v) p ρ(L, v) n+p dv dS p (K, u).Using Fubini's theorem, definition (3.12) of Φ µ p , and (2.13) yields(n + p)V n (L) 2 V p (K, Γ µ p L) = 1 n S n−1 h(Φ µ p K, v) p ρ(L, v) n+p dv = Ṽ−p (L, Φ µ, * p K). (5.7)Taking now K = Γ µ p L, we obtainV n (Γ µ p L) = 2 (n + p)V n (L)Ṽ−p (L, Φ µ, * p Γ µ p L).…”
mentioning
confidence: 99%